Selection of high-performance thermal interface materials for space payload applications - Yifan Zhang; Chunyan Liao; Junjun Qin; Yonglin Bai; Caixia Liu; Kun Zhen; Fujun Bai; Jiatao Wang (Case Studies in Thermal Engineering)
Thermal interface materials (TIMs) are crucial for the thermal management of space payloads. Based on the ASTM D-5470 test standard, a test setup was developed to investigate the effects of interface temperature, contact pressure, and surface roughness on the interface thermal resistance (ITR) of graphite thermal conductive sheet (GTS), smooth indium foil, and embossed indium foil in this paper. The results show that the ITR of the different TIMs exhibits significant differences under different loading conditions. Both indium foil and GTS significantly reduced the ITR compared to that in the absence of TIM, with indium foil exhibiting superior ITR performance at low and medium pressures. The prefabricated embossed structure further reduces the ITR of indium foils, making them superior to smooth indium foil under all conditions. In aerospace payload thermal management, indium foils have superior ITR performance, and GTS is more advantageous in high-temperature environments, with ease of disassembly and resistance to cold welding. The TIMs selection and application strategies proposed in this paper can provide important engineering guidance for the thermal management of space payloads.